Dampak Restrukturisasi Utang Terhadap Kinerja Keuangan (Studi Kasus pada PT X) - Ririn Riani; Arie Apriadi Nugraha (Indonesian Accounting Literacy Journal, 2020)
The debt restructuring trend in Indonesia is increasing from year to year. However, there are not a few cases of companies experiencing bankruptcy after restructuring the debt. This indicates a moral hazard, a phenomenon that shows that debt restructuring is only used by companies to avoid or postpone default status without significantly improving the company's performance in accordance with the initial debt restructuring objectives. This study aims to determine the impact of debt restructuring on the financial performance of PT X in the period after debt restructuring. This research is a quantitative study using the Paired Sample T Test hypothesis. The research sample is the financial statements of PT Perkebunan Nusantara in 2014-2015 and 2017-2018. The results showed that debt restructuring did not improve the financial performance of PT X.